The Legal Status of a Bona Fide Purchaser of a Land Plot According to the Legislation of Kazakhstan and Germany: Comparative Analysis - MUKASHEVA, Anar Abaikhankyzy; SABIROV, Kamal Kanatkalievich; ALENOV, Marat Amradinovich; BEKISHEVA, Sabigul Dzhanabaevna (Journal of Advanced Research in Law and Economics; Vol 9 No 3(33) (2018): JARLE, Volume IX, Issue 3(33), Summer 2018DO - 10.14505//jarle.v9 3(33).31, 2018)
According to the legislation of the Republic of Kazakhstan, land plots are classified as real estate facilities. As a consequence, the norms regulating the legal status of a bona fide purchaser of a land plot are considered to be of great interest for a study. On the contrary, the very concept of real estate is absent in Germany, and real estate facilities are classified as land plots or objects equated to them in terms of the legal status. Nevertheless, the German legislation is facing problems with determining the legal status of a bona fide purchaser of a land plot. At the same time, there is a significant difference in the mechanism for resolving issues related to the rights of an owner of a land plot in Germany and Kazakhstan. The article provides a comparative analysis of the legal regulation of a bona fide purchaser of a land plot according to the legislation of the Republic of Kazakhstan and Germany.